POLSKI KODEKS RODZINNY Z 1950 R. CZY PRZEŁOM? - Fiedorczyk, Piotr (Zeszyty Prawnicze, 2016)
POLISH 1950 FAMILY CODE – A TURNING-POINT? Summary Shortly after World War II new Communist authorities unified civil law in Poland. It was based on drafts prepared before the war by the Codification Committee, so it was a good example of law based on European legal tradition. In 1948 political situation has changed and new civil law was declared as a “bourgeois” and it had to be changed to become “socialist”. Family law was replaced as the first one, and it was separated from civil code, like in the USSR. The draft was prepared together with Czechoslovakia. Among many changes, the most important were: new construction of matrimonial property relations (joint ownership of husband and wife), new regulation of divorce, equal position of children coming out of wedlock, new legal shape of adoption. Only joint property of husband and wife can be regarded as a turning-point, the other changes were not as important. In fact, real turning-point in Polish family law took place in 1945, when civil marriages and divorces were introduced.